Quantification of NV-centres in diamond for room-temperature maser - Sathian,J; Jonathan,Breeze BB; Frangeskou,A; Morley,G; Alford,NM (2019)
MASERs are devices that exploit stimulated emission to amplify electromagnetic waves at microwave frequencies. Their principal advantage over conventional (semiconductor-based) electronic amplifiers is lower noise. An optically-pumped, solid-state pentacence maser operating at room temperature in pulsed mode was demonstrated [1]. This was followed by the recent demonstration of a continuous maser at room temperature using colour centres (NV) in diamond [2] paving the way for a new class of masers that could find new applications in medicine, security and sensing, quantum computing/information processing.